Determinants of Suboptimal Hemoglobin Response to Oral Iron Supplementation among Pregnant Women with Anemia in Primary Midwifery Care - Adriana Bangun; Achmad Zulfikar Siregar; Eka Ristin Tarigan; Adelina Fitri Tanjung; Putri Yolanda Situmorang; Merry Lumban Gaol (Media of Health Research, 2025)
Background: Iron deficiency anemia remains a major public health problem during pregnancy, particularly in low- and middle-income countries. Although oral iron supplementation is the standard treatment in Indonesian primary midwifery care, many women fail to achieve an adequate hemoglobin response. Objective: This study aimed to identify determinants of suboptimal hemoglobin response, defined as a hemoglobin increase of less than 1 g/dL after 90 days of oral iron supplementation, among pregnant women with anemia in primary midwifery care in Medan. Methods: An analytical cross-sectional study with prospective hemoglobin follow-up was conducted in seven primary midwifery care units involving 286 pregnant women with mild-to-moderate anemia. Data were collected using structured questionnaires, dietary assessments, compliance records, and maternal health records. Hemoglobin levels were measured at baseline and after 90 days. Multiple logistic regression was performed to identify independent determinants. Results: Suboptimal hemoglobin response occurred in 42.3% of participants. Independent determinants included poor adherence to iron supplementation (AOR = 5.34), low dietary iron intake (AOR = 4.52), tea or coffee consumption after meals (AOR = 3.71), moderate baseline anemia (AOR = 3.29), fewer than four antenatal care visits (AOR = 2.84), and inadequate nutritional counseling (AOR = 2.56). Conclusion: Behavioral, nutritional, biological, and service-related factors jointly influence hemoglobin response. Strengthening adherence monitoring, nutritional counseling, and risk-based screening within primary midwifery care may improve treatment outcomes among pregnant women with anemia.